2015
DOI: 10.1177/2042018815599874
|View full text |Cite
|
Sign up to set email alerts
|

Effects on lipid profile of supplementation with vitamin D in type 2 diabetic patients with vitamin D deficiency

Abstract: Correction of vitamin D deficiency in type 2 diabetic patients decreases total cholesterol. Our results do not rule out reductions in LDL cholesterol, non-HDL cholesterol and triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Similar results were reported by various authors in their studies (11,12,13) . Wang et al also showed that raised levels of vitamin D were related with favorable lipid profile, whereas lower levels of vitamin D were related with atherogenic lipid profile (4) .…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were reported by various authors in their studies (11,12,13) . Wang et al also showed that raised levels of vitamin D were related with favorable lipid profile, whereas lower levels of vitamin D were related with atherogenic lipid profile (4) .…”
Section: Discussionsupporting
confidence: 82%
“…We found different data about influence of vitamin D on lipid status in literature 13,29,37 . All our patients had significantly decreased levels of total cholesterol and triglycerides after therapy.…”
Section: Discussionmentioning
confidence: 84%
“…Supplementation with 4000 IU/day vitamin D in postmenopausal women with type 2 diabetes mellitus (T2DM) for 6 months resulted in a significant decrease in serum triglyceride levels without affecting levels of other lipid profiles (Munoz-Aguirre et al, 2015). No significant change in circulating levels of triglycerides, LDL-and HDL-cholesterol was observed in patients with T2DM following supplementation with 16,000 IU of vitamin D orally once a week for 8 weeks (Ramiro-Lozano & Calvo-Romero, 2015). Favorable effects of vitamin D intake on markers of insulin resistance might be explained by its effect on calcium and phosphorus metabolism and through up-regulation of the insulin receptor genes (Maestro, Molero, Bajo, Davila, & Calle, 2002) and increased transcription of insulin receptor genes (Maestro et al, 2002).…”
Section: Discussionmentioning
confidence: 98%